Reproducible Brain Charts: An open data resource for mapping brain development and its associations with mental health - Shafiei, Golia; Esper, Nathalia B; Hoffmann, Mauricio S; Ai, Lei; Chen, Andrew A; Cluce, Jon; Covitz, Sydney; Giavasis, Steven; Lane, Connor; Mehta, Kahini; Moore, Tyler M; Salo, Taylor; et al. (Neuron (Cambridge, Mass.), 2025)
Mental disorders are increasingly understood as disorders of brain development. Large and heterogeneous samples are required to define generalizable links between brain development and psychopathology. To this end, we introduce Reproducible Brain Charts (RBC), an open resource that integrates data from 5 large studies of brain development in youth from three continents (N = 6,346). Bifactor models were used to create harmonized psychiatric phenotypes, capturing major dimensions of psychopathology. Following rigorous quality assurance, neuroimaging data were carefully curated and processed using consistent pipelines in a reproducible manner. Initial analyses of RBC emphasize the benefit of careful quality assurance and data harmonization in delineating developmental effects and associations with psychopathology. Critically, all RBC data-including harmonized psychiatric phenotypes, unprocessed images, and fully processed imaging derivatives-are openly shared without a data use agreement via the International Neuroimaging Data-sharing Initiative. Together, RBC facilitates large-scale, reproducible, and generalizable research in developmental and psychiatric neuroscience.